Idiopathic Sixth Nerve Palsy After Bimaxillary Surgery. Issue 1 (January 2015) - Şirinoğlu, Hakan; Güvercin, Emre; Çakmakoğlu, Çağri; Filinte, Gaye Taylan; Yeşiloğlu, Nebil; Bozkurt, Mehmet
<x xml:space="preserve">Abstract</x> Abstract This was a case of a 21-year-old female patient with a very rare and unexpected symptom "diplopia occurring due to the idiopathic sixth nerve palsy" encountered after 2 weeks following bimaxillary surgery performed for the correction of class III malocclusion deformity.